Editorial: Identity is Coming - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2024)
This editorial includes some comments on identity management, a necessary addition to the Internet and World Wide Web and a topic of recent discussion in Australia. The editorial also introduces the content of the June issue.